2013
DOI: 10.1007/s00018-013-1443-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of histone gene transcription in yeast

Abstract: Histones are the primary protein component of chromatin, the mixture of DNA and proteins that packages the genetic material in eukaryotes. Large amounts of histones are required during the S phase of the cell cycle when genome replication occurs. However, ectopic expression of histones during other cell cycle phases is toxic; thus, histone expression is restricted to the S phase and is tightly regulated at multiple levels, including transcriptional, post-transcriptional, translational, and post-translational. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 124 publications
3
80
0
Order By: Relevance
“…We here provide functional evidence that in the testis, retinoid signaling might control entry of the undifferentiated spermatogonia into S phase, and then promote spermatogonial differentiation. First, impaired retinoid signaling in germ cells causes the arrest of the undifferentiated spermatogonia into S phase, accounting for the blockage of spermatogonial differentiation, as evidenced by: (1) a significant accumulation of the undifferentiated spermatogonia in the G0/G1 phase occurred in germ-cell mutants whereas the differentiation of the undifferentiated spermatogonia into A 1 spermatogonia is blocked; (2) inhibition of RA synthesis by WIN18,466 resulted in a blockade of entry into S phase in the undifferentiated spermatogonia as previously suggested by van Pelt et al (van Pelt et al, 1995;van Pelt and de Rooij, 1990); (3) expression of a burst of replication-dependent core histone genes, whose expression is induced right before and during S phase (Kurat et al, 2014), was downregulated in the undifferentiated spermatogonia of germ-cell mutants; and (4) expression of Ccnd2 and E2f, key regulators for the progression from G1 to S phase (Bohnsack and Hirschi, 2004), was reduced in the germ-cell mutants. Second, during reinitiation of spermatogonial differentiation in WIN18,466-treated mice upon RA administration, early differentiating spermatogonia (STRA8-positive spermatogonia) enter into the S phase.…”
Section: Discussion Retinoid Signaling Directly Controls Spermatogonimentioning
confidence: 54%
See 2 more Smart Citations
“…We here provide functional evidence that in the testis, retinoid signaling might control entry of the undifferentiated spermatogonia into S phase, and then promote spermatogonial differentiation. First, impaired retinoid signaling in germ cells causes the arrest of the undifferentiated spermatogonia into S phase, accounting for the blockage of spermatogonial differentiation, as evidenced by: (1) a significant accumulation of the undifferentiated spermatogonia in the G0/G1 phase occurred in germ-cell mutants whereas the differentiation of the undifferentiated spermatogonia into A 1 spermatogonia is blocked; (2) inhibition of RA synthesis by WIN18,466 resulted in a blockade of entry into S phase in the undifferentiated spermatogonia as previously suggested by van Pelt et al (van Pelt et al, 1995;van Pelt and de Rooij, 1990); (3) expression of a burst of replication-dependent core histone genes, whose expression is induced right before and during S phase (Kurat et al, 2014), was downregulated in the undifferentiated spermatogonia of germ-cell mutants; and (4) expression of Ccnd2 and E2f, key regulators for the progression from G1 to S phase (Bohnsack and Hirschi, 2004), was reduced in the germ-cell mutants. Second, during reinitiation of spermatogonial differentiation in WIN18,466-treated mice upon RA administration, early differentiating spermatogonia (STRA8-positive spermatogonia) enter into the S phase.…”
Section: Discussion Retinoid Signaling Directly Controls Spermatogonimentioning
confidence: 54%
“…Interestingly, we found that the majority of transcripts of the replication-dependent core histone genes, histone cluster 1 (Hist1) (Osley, 1991;Kurat et al, 2014;Marzluff et al, 2002) were downregulated in germcell mutants ( Fig. 4C; Table S1).…”
Section: Inactivation Of Retinoid Signaling Blocks Entry Into S Phasementioning
confidence: 96%
See 1 more Smart Citation
“…1B to D). Spt10p, Swi6p, Swi4p, Mbp1p, and Swi2p are transcription factors and regulators involved in the expression of histone genes (48,49). We also included asf1⌬, rtt106⌬, rtt109⌬, cac1⌬, and H3K56R mutants in our analysis, since the corresponding genes and acetylation of lysine 56 of histone H3 are involved in chromatin assembly (50,51).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings here and previous work of others (Sanders et al 2004;Du et al 2006) suggest that the HHT1-HHF1 locus may indeed have a unique function in DNA damage. Histones are highly regulated at multiple levels including expression, localization, PTM, and degradation (reviewed in Kurat et al 2013). Whether the restoration of suppression by HHT1-HHF1 is relevant to precise histone levels or some other aspect of this locus's biology has yet to be determined.…”
Section: Analysis Of Dna Damage Sensitivity In Gas1 Cells Reveals Thamentioning
confidence: 99%